2008
DOI: 10.1002/ar.20740
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoid Tissue Ontogeny in the Mummichog, Fundulus heteroclitus

Abstract: Most studies that examine the ontogeny of lymphoid organ development in teleostean fishes use species of interest to aquaculture or genetic research and, to date, have focused strictly on marine or freshwater species. The mummichog, Fundulus heteroclitus, also known as the estuarine killifish, is a unique model for studies on developmental immunobiology, because it is euryhaline, has a high degree of thermal tolerance, and has a unique reproductive strategy. Embryonic and larval mummichogs were examined for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Previous studies have shown that recombination-activating genes are highly conserved in different types of fishes (Brinkmann et al 2004;Hunt & Rice, 2008) and are specifically expressed in the early stage of thymus development (Hunt & Rice, 2008;Iwanami et al 2008Iwanami et al , 2011. Therefore, in the present study, the position of the thymus in the early developmental stages was confirmed using the position of Rag1 in WISH of tilapia embryos.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Previous studies have shown that recombination-activating genes are highly conserved in different types of fishes (Brinkmann et al 2004;Hunt & Rice, 2008) and are specifically expressed in the early stage of thymus development (Hunt & Rice, 2008;Iwanami et al 2008Iwanami et al , 2011. Therefore, in the present study, the position of the thymus in the early developmental stages was confirmed using the position of Rag1 in WISH of tilapia embryos.…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies have shown that recombination‐activating genes are highly conserved in different types of fishes (Brinkmann et al. ; Hunt & Rice, ) and are specifically expressed in the early stage of thymus development (Hunt & Rice, ; Iwanami et al. , ).…”
Section: Discussionmentioning
confidence: 99%
“…However, as shown by the present study and by Lam et al (2002), expansion and rapid growth of the thymus takes place only during the juvenile period of zebrafish. This thymus development pattern appears to be more generally realized in teleost fish, with the thymus being the first lymphoid organ to differentiate morphologically (Davidson & Zon, 2004; Rombout et al, 2005; Seemann et al, 2015; Zapata et al, 2006) and becoming only functional in the juvenile period (Falk‐Petersen, 2005; Hunt & Rice, 2008; Lam et al, 2004; Mulero et al, 2007; O'Neill, 1989; Parichy et al, 2009; Tatner & Manning, 1983). This late onset of thymus development and adaptive immune systems appears to be expressed in all teleost species that have been studied to date.…”
Section: Discussionmentioning
confidence: 99%
“…The major lymphomyeloid organs of fishes are thymus, head kidney and spleen [20,21]. The ontogeny of the lymphomyeloid organs start developing within few hours post fertilization [22][23][24][25][26][27][28][29][30][31][32][33][34][35] (Table 1) but the sequence of development differs markedly among the freshwater, estuarine and marine species [25][26][27][28][29][30][36][37][38][39]. Thymus is the first organ to become lymphoid, followed by kidney and spleen [38].…”
Section: Immunity Of Brood Fishmentioning
confidence: 99%